Tafsir Tabi'in Patterns in the Meccan Madrasah Period - Illiya Fairuz; Hayin Farichah; Dhur Anni (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The interpretation of the Al-Quran cannot be separated from the series of links in the chain of interpretive narrations, as well as its maintenance from the Prophet's time until now. The Tabi'in Interpretation Period cannot be separated from the series of Interpretation journeys, the style of Tafsir at this time was motivated by the expansion of Islamic territory so that ulama at this time also spread to madrasas such as Mecca, Medina and Iraq. In Mecca the Ulama who initiated it was Abdullah Ibn Abbas, followed by several famous students including Sa'ad bin Jubair, Mujahid bin Jubair, Ikrimah Maula Ibn Abas, Thawus bin Kisan, and Atha'bin Abi Rabah. At this time, many interpretations had a riwayah style, but several interpretations emerged with ra'yu.